Fiscal Consolidation and Automatic Stabilization: New Results - Mathias Dolls; Clemens Fuest; Andreas Peichl; Christian Wittneben (Center for Economic Studies and ifo Institute (CESifo), 2019)
We analyze how the combined effect of automatic stabilizers and discretionary changes in tax-benefit systems have affected the cushioning of income shocks in the Euro zone and the EU-27 in the period 2007–2014. We propose a new summary measure of the combined effect of automatic stabilizers and discretionary policy changes based on micro data and counter-factual simulation. Discretionary fiscal policy supported the effects of automatic stabilizers in the years 2008 and 2009 but then became much more restrictive. For the Euro zone as a whole, the share of income shocks absorbed by the tax and transfer system declined from 48 percent in 2008 to 24 percent in 2011. For some of the countries most affected by the crisis, the stabilization effect was even negative in some years of the crisis, implying that the tax and transfer system amplified income shocks. We also compare our measure of stabilization to estimates based on macro data.
Keywords: E63; E62; H31; 330; automatic stabilizers; fiscal consolidation; fiscal policy